Synthesis and oxygen evolution reaction (OER) catalytic performance of Ni2−xRuxP nanocrystals: enhancing activity by dilution of the noble metal. Issue 33 (10th August 2017) - Liyanage, D. Ruchira; Li, Da; Cheek, Quintin B.; Baydoun, Habib; Brock, Stephanie L.
Abstract : Incorporation of Ru into Ni2 P nanoparticles moderates the redox behavior of Ni and lowers the kinetic barrier for water oxidation. Abstract : Aiming to create an efficient, less-expensive catalyst for the oxygen evolution reaction (OER), a synthetic protocol is developed to prepare ternary metal phosphide nanoparticles, Ni2− x Ru x P, incorporating Ru, a traditional catalyst for OER, and Ni, a highly active but inexpensive metal. Using solution-phase arrested-precipitation reactions, crystalline Ni2− x Ru x P particles could be realized for compositions up to x ≤ 1, whereas more Ru-rich compositions, including Ru2 P, were amorphous. For x ≤ 1, particles are spherical, of sizes that vary between 5 and 10 nm in diameter (with a clear decreasing trend as the Ru amount is increased), and samples exhibit narrow size distributions (polydispersity < 15%). In contrast, amorphous Ru-rich phases exhibit worm-like morphologies. ICP-MS data indicate the actual metal ratio closely follows the target ratio employed in the synthesis. OER electrocatalytic activity was evaluated for selected compositions over the entire synthesis range (0 ≤ x ≤ 2). Intriguingly, Ru2 P proved to be the least active phase (overpotential of 0.56 V at 10 mA cm −2 in 1.0 M KOH) with the best performance observed for the bimetallic Ni1.25 Ru0.75 P phase (overpotential of 0.34 V). The augmented activity at x = 0.75 is attributed, at least in part, to electronic activation of Ni by Ru, facilitating Ni oxidation and thus decreasing the kinetic barrier for OER.